Correlation between Cu precipitates and irradiation defects in Fe–Cu model alloys investigated by positron annihilation spectroscopy. (15th January 2016) - Jin, Shuoxue; Zhang, Peng; Lu, Eryang; Guo, Liping; Wang, Baoyi; Cao, Xingzhong
Abstract: The correlation between Cu precipitates and vacancy-like defects in three Fe–Cu model alloys, Fe–0.15%Cu, Fe–0.3%Cu and Fe–0.6%Cu, irradiated at 400 °C with hydrogen ions at doses from 0.045 to 0.45 dpa, were revealed by positron annihilation spectroscopy. The formation of vacancy-like defects surrounded by tiny Cu precipitates induced the increment of the S and W parameters after irradiation. The peak value of the relative W parameter (ΔW/W), as the high momentum information on Cu precipitates, located in the track region and decreased with irradiation dose increased from 0.045 dpa to 0.45 dpa. The information on high momentum depended on the coverage fraction of the defects by Cu atoms. The effect of the irradiation dose, the irradiation depth and the Cu content on the Cu coverage fraction of the defects has been investigated in the present work. Graphical abstract: Figure a shows the ΔW/W parameters of the Fe–0.3%Cu alloy irradiated with different dose. Compared to the pure Fe and not irradiated alloy, the increment of the ΔW/W parameters meant the vacancy-like defect surrounded by Cu atoms formed due to the aggregation of Cu-vacancy complexes. With the irradiation dose increased from 0.045 dpa to 0.45 dpa, the ΔW/W parameter decreased, which was due to the size increment of vacancy-like defects at 0.45 dpa. It could decrease the coverage fraction of the defects by Cu atoms and annihilations with the Cu core electrons. The information on high momentum depended on the coverage fraction of the defects by Cu atoms. The ΔW/W parameter increased with the increasing of Cu content, as shown in Figure b. The Cu content increasing in Fe–Cu alloys enhanced the coverage of the defects by copper atoms and increased the ΔW/W parameters.